Advanced microscopy to elucidate cardiovascular injury and regeneration: 4D light-sheet imaging. (October 2018) - Baek, Kyung In; Ding, Yichen; Chang, Chih-Chiang; Chang, Megan; Sevag Packard, René R.; Hsu, Jeffrey J.; Fei, Peng; Hsiai, Tzung K.
Abstract: The advent of 4-dimensional (4D) light-sheet fluorescence microscopy (LSFM) has provided an entry point for rapid image acquisition to uncover real-time cardiovascular structure and function with high axial resolution and minimal photo-bleaching/-toxicity. We hereby review the fundamental principles of our LSFM system to investigate cardiovascular morphogenesis and regeneration after injury. LSFM enables us to reveal the micro-circulation of blood cells in the zebrafish embryo and assess cardiac ventricular remodeling in response to chemotherapy-induced injury using an automated segmentation approach. Next, we review two distinct mechanisms underlying zebrafish vascular regeneration following tail amputation. We elucidate the role of endothelial Notch signaling to restore vascular regeneration after exposure to the redox active ultrafine particles (UFP) in air pollutants. By manipulating the blood viscosity and subsequently, endothelial wall shear stress, we demonstrate the mechanism whereby hemodynamic shear forces impart both mechanical and metabolic effects to modulate vascular regeneration. Overall, the implementation of 4D LSFM allows for the elucidation of mechanisms governing cardiovascular injury and regeneration with high spatiotemporal resolution.